GENERALIZED CONVETERS OF IMMITTANCE ON THE BASIS OF INJECTION-TRANSIT TIME GROUNDED SOURCE TRANSISTOR STRUCTURE - Lischinskaya, Ludmila; Buliga, Igor; Shvedyuk, Andriy; Filinyuk, Nikolay (Scientific Works of Vinnytsia National Technical University, 2015)
Properties of injection-flight transistor structure with a general source are analysed as the generalized transformer of immittance, the tables of transformation of immittance are got